Application of E-Tendering In Malaysian Construction Industry - Tan, Jeffrey Jia Ren; Suhana, Kamarudin (2016)
Electronic tendering has been assumed to be a more effective method compare with a traditional tendering method. However, most of the local projects are still adopting the traditional tendering method. The aim of this study is to investigate whether the contractors in Malaysia construction industry would adopt and participate in the e-tendering system. The study will take into account the application of e-tendering in current Malaysia construction industry, the challenges of implementing the e-tendering system and willingness of the contractors to participate in e-tendering. The research applied quantitative data, which questionnaire survey had been distributed via online to identify the level of understanding about the e-tendering system of contractors in Malaysia and also whether the contractors involved in the application of e-tendering in Malaysia. The result shows that the application of e-tendering is in moderate level in current Malaysia construction community. The majority of the contractors have a moderate understanding regarding the e-tendering system and more than half of them having experience with e-tendering. The challenges of the e-tendering system and the contractor’s readiness in adopting e-tendering were evaluated. Most of the contractors are willing to involve if they are invited to participate in the e-tendering project. Saving in storage space is one of the biggest factors which contribute to the contractors' willingness to participate in e-tendering. In the other hand, security concern is the most important factor contributes to contractors' unwillingness in the participation of e-tendering.